FENOMENOLOGI KONSTRUKSI SOSIAL PADA KIAI YANG BERPOLITIK PRAKTIS - Mohammad Adi; Moh. Fudholi; Ridan Muhtadi (LP2M IAI Miftahul Ulum Pamekasan, 2021)
Kiai is an elite who has a very respectable position and is influencing the development of Islamic society. Kiai in Indonesia has become one of the strategic elite and is a figure who has a wide and deep knowledge of Islamic teachings. At this point can be seen the strategic roles of kiai in the context of socio-political life in Bangkalan Madura. Based on the study, it was found that the kiai proved to be the number of re-enumerators for the sake of the social conditions it faced, albeit still using the medieval style of thought. in general kiai concentrate on the world of education, social-political relations tend to be abandoned, so that when the flow of globalization emerged, many stuttering kiai responded. It is analyzed by using theory. Berger's social is referred to by the social framework in society. The research method used is qualitative phenomenology where data with observation and depth interview. The results of this study show the mindset of the people to construct the kiai politics and the factors that underlie the central role of kiai and politics.